ETHNO-BOTANICAL IDENTIFICATION OF SOME WILD HERB SPECIES OF SURKANDA DEVI HILL, UTTARAKHAND - Rishi, *Arya; D.C, Singh; R.C, Tiwari; Harsh Bardhan, Naithani (International Journal of Ayurveda and Pharma Research, 2016)
Medicinal plants play important role in healthcare practices among the tribal's and rural people. These Tribal's and rural people have wonderful knowledge about the effective treatment of many health problems only by using the plant parts. This knowledge acquired by the tribal's and rural peoples usually passed from generation to generation only in verbal form. So an effort was carried out to assess ethno botanical information of some wild herb species used by the local dwellers of Surkanda Devi Hill in District Tehri Garhwal of Uttarakhand. The information presented in this paper was gathered by frequent field visit in the forest and adjoining villages, participatory observations, group discussion, interviews with local knowledgeable people residing nearby Surkanda Devi Temple from September 2014 to March 2016. A total of 60 plant species were collected during the field visit out of which 48 plant species under 41 genera and 30 families were reported ethno-medicinal by the local dwellers and used by them for their primary health care. The plants used for different purposes are listed with scientific name, family, local name, ethno-medicinal importance. It can be concluded from this study that local dwellers of Surkanda Devi Hill inherit a rich traditional knowledge about the medicinal use of plants and documentation of this knowledge will open the door for new pharmacological research.